CE-47 Molecular imaging of the kidney in lupus nephritis to characterise response to treatment. (31st August 2016) - Parikh, Samir V; Malvar, Ana; Song, Huijuan; Alberton, Valeria; Lococo, Bruno; Vance, Jay; Zhang, Jianying; Yu, Lianbo; Birmingham, Dan; Rovin, Brad H
Abstract : Background: The response of lupus nephritis (LN) to treatment is assessed by clinical criteria, usually proteinuria and renal function, alone. The consequences of treatment for the kidney at the molecular level have not been explored in human LN, but could have important implications for modifying therapy to improve renal outcomes in LN. In this investigation changes in intra-renal transcript expression were measured and correlated with response in a LN cohort that underwent serial kidney biopsies. Methods: SLE patients suspected of having LN had a kidney biopsy for diagnosis (Bx1) and patients with proliferative LN (n = 19) were induced with high-dose corticosteroids plus either MMF or cyclophosphamide. After completing induction therapy, approximately 6 months, patients had a second kidney biopsy (Bx2) to determine histologic response to therapy. Intra-renal transcript expression was measured in Bx1 and B × 2 using Nanostring technology and a panel of over 500 immune response genes. Patients were segregated by clinical response at 6 months into group of complete responders (n = 5, CR) and a group of non-responders (n = 4, NR). Changes in transcript expression were compared between Bx1 and B × 2 in each responder group and between responder groups. Results: Compared to healthy control kidneys (pre-implantation living donor transplant kidney biopsies, n = 4), the CR group had 21 differentially-expressed transcripts at B × 1 and 28 at B?× 2. In contrast the NR had 45 and 103 differentially-expressed transcripts at B × 1 and B × 2, respectively, compared to controls. The profiles of these differentially-expressed genes indicated that the type 1 interferon, the alternative complement and T cell signalling pathways discriminated CR from NR. At B?× 1 transcripts regulated by type 1 interferon were over-expressed in CR and NR. During induction therapy the expression of type 1 interferon-inducible genes declined in CR but increased in NR, and additional type 1 genes were activated. Similarly, complement component transcript expression was increased at B × 1 in CR and NR and transcripts for regulators of the alternative pathway were suppressed in NR. At B × 2, these complement transcripts normalised in CR, but increased expression in NR. Transcripts related to T cell signalling became overexpressed at B × 2 in NR; this occurred to a lesser extent in CR. To determine whether changes in intra-renal transcript expression translated to changes in protein expression that could be measured non-invasively, complement component C5a was measured in the urine of an independent cohort of LN patients (n = 34). Urine C5a concentration was significantly higher than normal in CR and NR at LN flare. After treatment urine C5a fell significantly in CR, but remained elevated in NR. Conclusion: These data demonstrate that activity of intra-renal inflammatory genes induced at LN flare begins to fall in patients who respond clinically to induction therapy, but increases in patients who do not respond. The functional profiles of the protein products of these transcripts suggest that non-responders may benefit from interventions targeted at the type 1 interferon, alternative complement and T cell signalling pathways.